Study of Coronary Atherosclerosis by Modified American Heart Association Classification of Atherosclerosis-An Autopsy Study - Viral M. Bhanvadia; Nandini J. Desai; Neeru M. Agarwal (Journal of Clinical and Diagnostic Research, 2013)
Background: The study was designed to assess the atherosclerotic lesions in coronary arteries in cases subjected to autopsy to grade by applying Modified American Heart Association (AHA) classification, evaluate the atheromatous & vulnerable plaques to find out the to age and sex related prevalence of atherosclerosis in the semi-urban & urban population of Jamnagar, a district in Western India. Material & Methods: Autopsy was conducted on 264 cases whose age ranged from 8-79 years, by the conventional technique; heart was removed & dissected along the direction of blood flow. Microscopic assessment of the three main coronary arteries was done. Result: According to Modified AHA classification of atherosclerosis, maximum number of cases were in the 40-49 years age group. Intimal xanthoma was the most common type in all three coronary arteries. The number of males was 168(64%) and females was 96(36%). 59% males & 52% female were affected from atherosclerosis. An intermediate lesion was noted commonly in young individuals (10-39 years) and older individuals (40-79 years) were 46% & 41% respectively. Pathological Intimal thickening was more common in left anterior descending coronary artery compared to others. Thin fibrous cap atheroma was more common in Left circumflex artery than compared to Left anterior descending artery & Right coronary artery. Conclusion: The study highlights the impact of atherosclerotic lesions in the population of Jamnagar, a district in Gujarat state of Western India. The increased amount of intermediate atherosclerotic lesions found in the young population gives an indication that anti-atherogenic preventive measures and drastic dietary & life style modification need to be implemented in young individuals, this will help to prevent coronary artery disease from causing premature death that lead to huge financial burden on the economy and health sector of India.